2023
DOI: 10.3390/fermentation9060527
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Identification of EPS Produced by Five Lactic Acid Bacteria and Evaluation of Their Effects on the Texture of Fermented Goat Milk

Gengdian Liu,
Guowei Shu,
Jiansheng Wang
et al.

Abstract: Extracellular polysaccharide (EPS) produced by five lactic acid bacteria (Limosilactobacillus fermentum B55, Limosilactobacillus fermentum B62, Lactiplantibacillus plantarum 7830, Pediococcus acidilactici B30, and Lactobacillus helveticus K2) were purified and identified, and their effects on the texture of fermented goat milk were evaluated. The purified EPS fractions EPS 1a, EPS 2b, EPS 3c, EPS 4d, and EPS 5e of strains B62, 7830, K2, B55, and B30 were obtained with ion exchange chromatography, and their mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…It was confirmed that the EPS from strain L3 T consists mainly of glucose and some mannose, which may be heteropolysaccharides. It is similar to EPSe5 produced by lactic acid bacteria but has a slightly different monosaccharide composition ( Liu et al., 2023 ). Additionally, the monosaccharide composition of EPS produced by strain L3 T suggests that it is different from EPS produced by other strains ( Kim et al., 2022 ; Liu et al., 2023 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was confirmed that the EPS from strain L3 T consists mainly of glucose and some mannose, which may be heteropolysaccharides. It is similar to EPSe5 produced by lactic acid bacteria but has a slightly different monosaccharide composition ( Liu et al., 2023 ). Additionally, the monosaccharide composition of EPS produced by strain L3 T suggests that it is different from EPS produced by other strains ( Kim et al., 2022 ; Liu et al., 2023 ).…”
Section: Discussionmentioning
confidence: 97%
“…It is similar to EPSe5 produced by lactic acid bacteria but has a slightly different monosaccharide composition ( Liu et al., 2023 ). Additionally, the monosaccharide composition of EPS produced by strain L3 T suggests that it is different from EPS produced by other strains ( Kim et al., 2022 ; Liu et al., 2023 ). EPS produced by microorganisms is regulated by several genetic factors, carbon sources, and environmental variables and may differ in composition from EPS produced by other strains, even of the same species ( Pachekrepapol et al., 2017 ).…”
Section: Discussionmentioning
confidence: 97%
“…The use of different nutrients as culture media for lactic acid bacteria may yield exopolysaccharides with different molecular weights, different chemical structures, and different biological properties. Liu et al (2023) isolated different exopolysaccharides produced from goat milk through fermentation with five lactic acid bacteria (Limosilactobacillus fermentum B55, Limosilactobacillus fermentum B62, Lactiplantibacillus plantarum 7830, Pediococcus acidilactici B30, and Lactobacillus helveticus K2). Their results demonstrate that lactic acid bacteria can promote acid production and improve the texture of fermented goat milk, as well as increase the acidity, hardness, consistency, and viscosity of the product [4].…”
mentioning
confidence: 99%
“…Liu et al (2023) isolated different exopolysaccharides produced from goat milk through fermentation with five lactic acid bacteria (Limosilactobacillus fermentum B55, Limosilactobacillus fermentum B62, Lactiplantibacillus plantarum 7830, Pediococcus acidilactici B30, and Lactobacillus helveticus K2). Their results demonstrate that lactic acid bacteria can promote acid production and improve the texture of fermented goat milk, as well as increase the acidity, hardness, consistency, and viscosity of the product [4]. In addition to pure plants and pure dairy products, products that are mixed with plants and dairy products and then fermented with lactic acid bacteria have also been developed, such as mixed barley and milk fermented with lactic acid bacteria.…”
mentioning
confidence: 99%